Draft Genome Sequence of Halomonas sp. Strain KAO, a Halophilic Mn(II)-Oxidizing Bacterium - Lee, Cameron J. (Microbiol Resour Announc, 2021)
Halomonas sp. strain KAO is an aerobic, Mn(II)-oxidizing, halophilic bacterium. The draft genome of the isolate contains 47 contigs encompassing 3.7 Mb and a GC content of 64.22%. This sequence will provide essential information for future studies of Mn(II) oxidation, particularly under halophilic conditions.